EFFECT OF CIPC TREATMENT ON POST-HARVEST LOSSES AND PROCESSING ATTRIBUTES OF POTATO CULTIVARS - Mehta, Ashiv; Singh, Brajesh (Potato Journal, 2015)
Considerable quantities of potato (Solanum tuberosum L.) are transported to different consumer centers through out the country and also exported to neighboring countries. Sprouting of potatoes is the major post-harvest limiting factor. Sprout inhibition treatment with isopropyl 3-chlorophenyl carbamate (CIPC) was evaluated under ambient conditions (20 to 35Â°C, 44 to 86% RH) in five potato varieties viz. Kufri Chipsona-1, Kufri Surya, Kufri Jyoti, Kufri Pukhraj and Kufri Bahar after harvest and after storage at 2-4Â°C for four months. CIPC treatment (15 and 20 mg a.i./kg tuber weight) significantly reduced sprouting and total losses in freshly harvested potatoes of all the varieties up to 60 days. Whereas in cold stored potatoes, CIPC treatment was effective at higher concentrations (25 and 30 mg a.i. /kg tuber weight) in only two varieties. Nevertheless, the treatments could usefully extend the shelf life of potatoes by 30 to 45 days. CIPC treatment reduced sugar contents and improved the chip colour. Freshly harvested potatoes of Kufri Chipsona-1 can be marketed as table as well as processing potatoes, while other cultivars were suitable for table purpose only. Cold stored potatoes can be marketed only as table potatoes. CIPC residues were below the permissible limits and potatoes were safe for human consumption. The information is of high practical utility to market/export potatoes to distant markets.